The Role of Mesh Generation, Adaptation, and Refinement on the Computation of Flows Featuring Strong Shocks. (22nd April 2012) - Bonfiglioli Bonfiglioli, Aldo Aldo; Paciorri Paciorri, Renato Renato; Di Mascio Di Mascio, Andrea Andrea
Abstract : Within a continuum framework, flows featuring shock waves can be modelled by means of either shock capturing or shock fitting. Shock-capturing codes are algorithmically simple, but are plagued by a number of numerical troubles, particularly evident when shocks are strong and the grids unstructured. On the other hand, shock-fitting algorithms on structured grids allow to accurately compute solutions on coarse meshes, but tend to be algorithmically complex. We show how recent advances in computational mesh generation allow to relieve some of the difficulties encountered by shock capturing and contribute towards making shock fitting on unstructured meshes a versatile technique.